Etyczne i ekonomiczne aspekty programu agrarnego Henryka Kamieńskiego - Szymański, Zdzisław (Annales. Etyka w Życiu Gospodarczym, 2008)
Henryk Kamieński (1813–1866), a philosopher, economist, and theorist of struggle for national independence, idealized petty ownership as the most appropriate form of ownership both in ethical and economic aspects. He analyzed the problem on three levels. In his proposals for a specific solution of the agrarian question, presented in the Warsaw periodicals, Kamieński supported the introduction of agricultural rent paid by peasants and the abolishment of serfdom. Calling serfdom a land usury had an ethical implication. In the protection of the manor over peasants Kamieński sees the desire of manor owners to hold the victims of this usury in their hands. Replacement of serfdom with an agricultural rent was for him the first step in granting landownership to peasants. Kamieński emphasizes that petty ownership is conducive to production growth. He believes that the spread of it is an opportunity for peasants to heighten their national consciousness and a chance of civilized advancement of Polish territories. This line of thinking is clearly evident in his studies published abroad, devoted to the conception of combining a national uprising with granting freehold to peasants. Kamieński also discusses the values of petty ownership in agriculture in his theoretical work Filozofia ekonomii materialnej ludzkiego społeczeństwa [Philosophy of material economics of human society], in which he presents his vision of a system of social justice. For him, petty ownership is a guarantee of respect for human rights, the most effective safeguard of preserving the autonomy of human individual. In this reasoning we could see certain elements of personalism, which brings Kamieński’s standpoint closer to that of Pope John Paul II.